2020
DOI: 10.1177/2473974x20978137
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Inflammation‐Based Prognostic Scores on Survival in Patients With Hypopharyngeal Squamous Cell Carcinoma

Abstract: Objective To investigate the predictive accuracies of the modified Glasgow Prognostic Score (mGPS), neutrophil-lymphocyte ratio (NLR), and platelet-lymphocyte ratio (PLR) as prognostic factors for patients with hypopharyngeal squamous cell carcinoma (HSCC). Study Design Retrospective study. Setting University hospital. Methods The records of 106 patients who were histologically diagnosed with HSCC between January 2007 and December 2017 were reviewed. mGPS, NLR, and PLR were analyzed; univariate and multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Another study also identified a significant association between a high HS-mGPS and a larger tumor size and higher grade of soft tissue sarcoma ( 31 ). A study on hypopharyngeal cancer detected no significant correlation of the GPS with patients’ clinicopathological characteristics ( 49 ). By contrast, we revealed an HS-mGPS of 1−2 to exhibit a significant correlation with advanced-stage disease, more advanced T and N stages, ENE, and a DOI of ≥10 mm, suggesting that the HS-mGPS may have high sensitivity for predicting head and neck cancer aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also identified a significant association between a high HS-mGPS and a larger tumor size and higher grade of soft tissue sarcoma ( 31 ). A study on hypopharyngeal cancer detected no significant correlation of the GPS with patients’ clinicopathological characteristics ( 49 ). By contrast, we revealed an HS-mGPS of 1−2 to exhibit a significant correlation with advanced-stage disease, more advanced T and N stages, ENE, and a DOI of ≥10 mm, suggesting that the HS-mGPS may have high sensitivity for predicting head and neck cancer aggression.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Several studies have also investigated the association between the mGPS and outcomes among patients with head and neck cancer. Nakayama et al 13 were the first to report the prognostic value of the mGPS in this setting, and Iuchi et al 5 subsequently reported that combining the mGPS and conventional TNM staging provided more accurate prognostication. In addition, Chen et al 14 have reported that the GPS may have prognostic value and guide personalized treatment among patients with metastatic nasopharyngeal carcinoma who received cisplatin-based palliative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Nakayama et al were the first to report the prognostic value of the mGPS in this setting, 16 and Iuchi et al subsequently found that combining the mGPS and conventional TNM staging provided more accurate prognostication. 7 In addition, Chen et al noted that the GPS may have prognostic value and guide personalized treatment among patients with metastatic nasopharyngeal carcinoma who received cisplatin-based palliative chemotherapy. 17 The present study revealed that the mGPS was useful for predicting outcomes among patients with HSCC.…”
Section: Discussionmentioning
confidence: 99%